PENGAPLIKASIAN MASKER EKSTRAK ESSENSIAL OIL MAWAR PADA JENIS KULIT KERING UNTUK USIA SETENGAH BAYA - Rohana Rohana (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACTSkin problem is often a problem that is concidered to be able to reduce someone  apperances of ourselves. Because the presence of skin problems that often make us less confident especially in midlife who have less manicured facial skin absortion has begun to decrease, the muscles begin to slack and sebaceous glands do not produce enough to the skin. For that, we need skin care facial masks made from natural extract such as  rose essential oil that can tighten the skin, smooth the skin and flavorful therapeutic natural ingredients that can be reasuring and soul. By doing regular maintenance such us the use of essentialf rose masks corresponding to the facial skin muddle-aged women, it is expected that midle-aged woman’s skill will be moist or dryness level can be decreased so that the skin also can absorb moisture for the skin, and  attention to good diet and vitamin intake of nutritions for the body, a healthy lifestyle and avoid things that can dry out tke skin should be done. Kata Kunci : Masker, jenis kulit kering, usia setengah baya